PRODUCTION PERFORMANCE AND BLOOD PROFILE OF CLIMBING PERCH Anabas testudineus Bloch CULTURED IN PEAT POND WITH DIFFERENT STOCKING DENSITIES - Ani Widiyati; Adang Saputra; Eri Setiadi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2019)
Climbing perch is one of economically-valued local fish in Indonesia, particularly in Borneo, Sumatra, and Java Islands. The fish has the potential to be developed as freshwater aquaculture species. The purpose of this experiment was to evaluate the production performance and blood profile of climbing perch cultured in peat pond with different stocking densities. The research was conducted in Kereng Bangkiray Village, Sebangau District, Palangkaraya City, Central of Borneo. Nine fish ponds sized 5.0 m x 5.0 m x 1.5 m were used. Nets with a mesh size of 1 cm measuring 2.0 m x 1.5 m x 1.0 m was installed in each fish pond for the experiment. The treatment consisted of different stocking densities, namely 15 fish/m2, 30 fish/m2, and 45 fish/m2. Fish with the body weight of 20 ± 1.25 g were used. Fish were cultured for four months. An artificial diet containing 30% protein was given with a feeding rate of 5%. The experiment was designed in a complete randomized design. The result showed that the production performances (i.e. survival, specific growth rate, absolute weight, and biomass) were significantly higher at the densities of 15 and 30 fish/m2 than that of 45 fish/m2 (P<0.05). Blood profile such as glucose, erythrocyte, leucocyte, and hemoglobin were higher at the density of 45 fish/m2 except for hematocrit which was higher at the densities of 30 and 15 fish/m2. Water quality parameters such as dissolved oxygen, nitrite, nitrate, and ammonia at the densities of 15 and 30 fish/m2 showed better values than that of 45 fish/m2 stocking density. To optimize the productivity and maintain the optimum water quality condition, the optimal stocking density for climbing perch culture is suggested at 30 fish/m2.